Knowledge, attitude and practices of pediatricians regarding the prevention of oral diseases in Italy - Marinelli Alessandra; Nobile Carmelo GA; Di Giuseppe Gabriella; Angelillo Italo F (BMC, 2006)
Abstract Background Pediatricians are in an ideal position to advise families about the prevention and management of oral diseases in children. The objective of the study was to determine knowledge, attitude, and practices regarding the prevention of oral diseases among pediatricians in Italy. Methods A systematic random sample of 1000 pediatricians received a questionnaire on socio-demographic and practice characteristics; knowledge on risk factors; attitude and practices towards the prevention of oral diseases. Results A total of 507 pediatricians participated. More than half knew the main risk factors for oral diseases and this knowledge was higher in primary care pediatricians (p = 0.007), in those with a higher number of hours worked per week (p = 0.012), and who believed that oral diseases may be prevented (p = 0.017). Pediatricians with higher knowledge about the main risk factors (p = 0.006) believe that they have an important role in preventing oral diseases and that they can perform an oral examination. Almost all (89%) prescribed fluoride supplements and those younger (p = 0.016), with a higher number of patients seen in workday (p = 0.001), with longer practice activity (p = 0.004), those who believe that fluoride is effective in preventing caries (p < 0.0001), and who learned about prevention from scientific sources (p = 0.002) were more likely to prescribe fluoride. One-fourth and 40.6% provides and recommends a dental visit once a year and primary care pediatricians (p = 0.014) and those who believed that routine visit is important in preventing oral diseases (p < 0.0001) were more likely to recommend a dental visit once a year. Conclusion The results showed a lack of knowledge among pediatricians although almost all believed that they had an important responsibility in preventing oral diseases and provided an oral examination.